Researching the performative interface in Rapa Nui: bridging Indigenous knowledges, colonial histories and contemporary performances - Fortin Cornejo, Moira (Frontiers in Research Metrics and Analytics, 2025)
My research focuses on the performing arts in Rapa Nui. I am interested in performances as ways of navigating and negotiating the complex intersections between traditional/Indigenous and contemporary/Western cultural identities. As a non-Indigenous researcher who has collaborated extensively with the Rapa Nui community, I have had to navigate the interface, learning about and engaging in diverse knowledge systems and methods. The idea of engaging with both Western and Indigenous epistemologies, reflects my belief that both bodies of work can complement one another, and reflects my desire to look at research questions from a range of different angles and perspectives, welcoming and accepting the differences and similarities between worldviews, enriching the possibilities for dialogue between cultures. My research ethos consciously focuses on the positives of cultural dialogue, with a desire to better understand and support intercultural theater practices in Rapa Nui. In my research I have utilized open-ended interviews, framed by Talanoa which is an Indigenous Pacific research methodology which involves deep, open ended discussions and listening, valuing and learning from what is shared in these dialogues and prioritizing relationships between people over rigid, predetermined research agendas. My interactions with the Rapa Nui communities have explored their perceptions of what constitutes “traditional” and contemporary theater/performance practices. The genealogy and influence that “tradition”, as a colonial term, has had over Rapa Nui performing arts over time and space are explored in this article. Colonial histories have effected how contemporary performing arts have been articulated, conceptualized, produced and taught in twenty first century Rapa Nui.